2018
DOI: 10.1021/jacs.8b10298
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt-Catalyzed Trifluoromethoxylation of Epoxides

Abstract: A catalytic ring-opening reaction of epoxides by nucleophilic trifluoromethoxylation of trifluoromethyl arylsulfonate has been developed based on the use of a cobalt catalyst. This reaction provides an efficient, simple route for directly construction of a wide range of vicinal trifluoromethoxyhydrins under mild conditions. In addition, this method can convert terminal epoxides into target products with good chemo-and regioselectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 76 publications
2
20
0
Order By: Relevance
“…The bis(trifluoromethylthiolated) product 2a was produced in high yield (Scheme 3, top), which indicated that this 1,2-bis(trifluoromethylthiolation) of epoxides probably proceeded through tandem ring-opening and deoxytrifluoromethylthiolation processes. On the basis of the above result and previous reports, [9,11,12,22] a reasonable mechanism is proposed (Scheme 3, bottom). First, the activation of AgSCF 3 generates -SCF 3 , which attacks the epoxide 1 to deliver alkoxide intermediate A.…”
Section: Resultssupporting
confidence: 79%
“…The bis(trifluoromethylthiolated) product 2a was produced in high yield (Scheme 3, top), which indicated that this 1,2-bis(trifluoromethylthiolation) of epoxides probably proceeded through tandem ring-opening and deoxytrifluoromethylthiolation processes. On the basis of the above result and previous reports, [9,11,12,22] a reasonable mechanism is proposed (Scheme 3, bottom). First, the activation of AgSCF 3 generates -SCF 3 , which attacks the epoxide 1 to deliver alkoxide intermediate A.…”
Section: Resultssupporting
confidence: 79%
“…The trifluoromethoxide group has become an emerging feature in pharmaceuticals, agrochemicals, and materials. In pharmaceuticals, trifluoromethyl ethers often exhibit improved drug properties including increased lipophilicity and metabolic stability, and can adopt unique conformations when compared with aliphatic ethers . The inclusion of a trifluoromethyl ether can also increase the potency of a drug lead .…”
mentioning
confidence: 99%
“…The reaction was scalable and tolerated a wide range of functional groups. Cobalt-catalyzed trifluoromethoxylation of epoxides 68 was achieved by activation of TFMS 57 (Scheme 40) with 2,4-dinitrophenates [134]. The use of n-Bu 4 N + DNP − instead of fluorides to activate TFMS 57 enhanced nucleophilicity and stability of trifluoromethoxy anion as well as avoided formation of fluorinated byproducts.…”
Section: Trifluoromethyl Arylsulfonates (Tfms)mentioning
confidence: 99%